Aspects of Solinus' Collectanea rerum memorabilium - Belanger, Caroline (Université d'Ottawa / University of Ottawa, 2014)
Solinus’ Collectanea rerum memorabilium, composed in the third or fourth century, was an esteemed work of travel and natural history throughout Late Antiquity and the Middle Ages. Although scholars since the early Enlightenment have criticised this work as an unoriginal compilation of earlier sources, Solinus’ skill in selecting and organising information, and his book's influence throughout much of western history, cannot be denied. The first chapter argues that Solinus designed his book to have wide appeal, so as to entertain and educate the greatest possible audience. No previous English or French scholarship has addressed Solinus’ book as a fundamentally entertaining work, but there are many indications that it would be considered a fashionable and amusing informational text by the elite class. By drawing on several highly respected genres, frequently citing received authorities, and writing in a flowing discourse, Solinus presents information about worldwide wonders, of no immediate use to the average Roman, as though it were beneficial and even necessary to the educated reader. The second chapter looks closely at Solinus’ literary technique, then considers him in the context of three other encyclopedic authors: Aulus Gellius in the second century, and Macrobius and Martianus Capella in the fifth. The third chapter examines the Collectanea as a work of imperial literature. I argue for the novel claim that Solinus’ depiction of the Macrobian Ethiopians seems to associate them with his contemporaries, the Axumites. His portrayal of the Macrobians shows that although on the surface the book adheres to Romano-centric literary traditions, in subtle ways it reflects its contemporary context and Solinus’ own perspective. By examining the text itself as well as the context in which it was created and received, this thesis contributes to a new understanding of the Collectanea’s value as a work of literary and historical significance.
Keywords: Solinus; Classical Studies; Roman Literature; Roman History; Rome